Accumulation of polyethylene microplastics induces oxidative stress, microbiome dysbiosis and immunoregulation in crayfish. Issue 125 (June 2022) - Zhang, Xiaowen; Jin, Zeyu; Shen, Manli; Chang, Zhongjie; Yu, Guoying; Wang, Lan; Xia, Xiaohua
Abstract: Microplastics have become a worldwide pollutant, widely discovered in soil, air and aquatic environment. Microplastics have been found in habitats where crayfish ( Procambarus clarkii ) cultivated, but the impact of microplastics on crayfish remains unclear. In this study, after 21-day dietary exposure, polyethylene (PE) particles were found to accumulate in intestine, hepatopancreas, gills and hemolymph of crayfish. Furthermore, PE particles can still be detected in these tissues after a 7-day depuration in clean water. PE retained in these tissues caused oxidative stress responses, as indicated by the change of oxidative-stress-related index, such as the increase of H2 O2 level and SOD activity. PE exposure also caused hemocytic encapsulation in crayfish hepatopancreas and increase of mucus secretion in intestine. Moreover, PE exposure affected the microbiota balance in crayfish, by reducing the total microbiota abundance and altering the proportions of many bacterial families. Interestingly, results showed that PE exposure led to of lower numbers of hemocytes and declination of phenoloxidase activity. Finally, PE exposure induced the expression of immune-related genes, including transcription factors and antimicrobial peptides. Taken these together, we conclude that PE microplastics exert considerable toxic effects on crayfish and are a potential threat to crayfish aquaculture and consumption. This study provides basic toxicological data toward quantifying and illuminating the impact of PE microplastics on freshwater animals. Graphical abstract: Image 1 Highlights: Polystyrene microplastics accumulated in several tissues of crayfish and caused histopathological changes. Polystyrene microplastics induced oxidative stress and immune responses in crayfish. Polystyrene microplastics induced gut microbiota dysbiosis in crayfish.